WPF programmer's reference Windows presentation foundation with C♯ 2010 and .NET 4 - Stephens, Rod 1961- (Wiley, 2010)
The books included in this set are: 9780470502204 Professional ASP.NET 4: in C# and VB: Written by three highly recognized and regarded ASP.NET experts, this book provides comprehensive coverage on ASP.NET 4 with a unique approach featuring examples in both C# and VB, as is the incomparable coverage of core ASP.NET. 9780470502259 Professional C# 4 and .NET 4: After a quick refresher on C# basics, the author dream team moves on to provide you with details of language and framework features including LINQ, LINQ to SQL, LINQ to XML, WCF, WPF, Workflow, and Generics. 9780470548653 Professional Visual Studio 2010: This book gets you quickly up to speed on what you can expect from Visual Studio 2010. Packed with helpful examples, this comprehensive guide explains examines the features of Visual Studio 2010, which allows you to create and manage programming projects for the Windows platform. 9780470499832 Visual Basic 2010 Programmer's Reference: This reference guide provides you with a broad, solid understanding of essential Visual Basic 2010 topics and clearly explains how to use this powerful programming language to perform a variety of tasks 9780470477229 WPF Programmer's Reference: Windows Presentation Foundation with C# 2010 and .NET 4: Written by a leading expert on Microsoft graphics programming, this richly illustrated book provides an introduction to WPF development and explains fundamental WPF concepts. 9780470257029 Professional SQL Server 2008 Programming: This expanded best-seller includes new coverage of SQL Server 2008's new datatypes, new indexing structures, manageability features, and advanced time-zone handling.
Print version record
Keywords: Windows presentation foundation; Microsoft .NET Framework; Application software; Computer programming; C# (Computer program language); Logiciels d'application; Programmation (Informatique); C# (Langage de programmation); computer programming; COMPUTERS; General